2010
DOI: 10.1007/s00726-010-0749-2
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarianism, female gender and increasing age, but not CNDP1 genotype, are associated with reduced muscle carnosine levels in humans

Abstract: Carnosine is found in high concentrations in skeletal muscles, where it is involved in several physiological functions. The muscle carnosine content measured within a population can vary by a factor 4. The aim of this study was to further characterize suggested determinants of the muscle carnosine content (diet, gender and age) and to identify new determinants (plasma carnosinase activity and testosterone). We investigated a group of 149 healthy subjects, which consisted of 94 men (12 vegetarians) and 55 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
106
6
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 42 publications
6
106
6
8
Order By: Relevance
“…When comparing intramuscular carnosine between males and females, a 3.5 : 1.0 ratio exists respectively between genders (8). Females also require lower levels of BA supplementation to obtain similar relative increases in carnosine compared to males (9).…”
mentioning
confidence: 99%
“…When comparing intramuscular carnosine between males and females, a 3.5 : 1.0 ratio exists respectively between genders (8). Females also require lower levels of BA supplementation to obtain similar relative increases in carnosine compared to males (9).…”
mentioning
confidence: 99%
“…Similarly, a decline of 63% of M-HCD concentration in human patients with neuromuscular disease aged between 10 and 70 years has been reported [56]. Everaert et al, [58] found a negative correlation between age and carnosine concentration in the soleus muscle in humans. This represents a decline of soleus carnosine concentration of 1.2% each year, however the majority of participants were younger than 30 years of age.…”
Section: Agementioning
confidence: 62%
“…However, there was no correlation between free testosterone and M-Carn content found by Everaert et al [58] in young men. Also, the age-related changes in testosterone [67,68] are not the same as the age-related changes in M-Carn.…”
Section: Gendermentioning
confidence: 62%
See 2 more Smart Citations